Strategi Pengembangan Program Pemberdayaan Masyarakat Hutan Kemasyarakatan di Desa Gunung Silanu Kecamatan Bangkala Kabupaten Jeneponto - Nur Hikmah; Asar Said Mahbub; Supratman Supratman (Fakultas Kehutanan, Universitas Hasanuddin, 2018)
Community forestry development in Gunung Silanu village is capable of rebuilding deforestation-affected forest, but communities can not take advantage of the potential forests to improve their welfare. Therefore, a strategy for community forestry development is required. This study aims to analyze the success rate of community empowerment programs in community forest management, analyze the drivers and restraints of community forest management, and formulate strategies and action programs for community empowerment development. The study was conducted from February to May 2018 in the community forest area of Gunung Silanu Village. The data obtained were identified and reviewed using the criteria tables and indicators of community empowerment. Furthermor drivers and inhibitors were identified to determine the importance of each factor through expert studies. Finally, strategies and action programs were formulated for each factor. The results show that the empowerment of community forestry development in Gunung Silanu village succeeded with a score of 2.4. Nevertheless, there are several factors that hinder the management of community forest. Therefore, the inhibiting factors will be reduced and simultaneously the driving forces will be strengthened through strategies and action programs.